Penerapan Sistem Enterprise Resource Planning (ERP) Pada Perusahaan Jasa Service PT XYZ - Bagus Wahyu Masdhana; Rizqi Novita Sari (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
This research aims to apply the Enterprise Resource Planning (ERP) system in the context of procuring materials to support services at PT. XYZ. The implementation process begins with problem identification, literature study, data collection, identifying Odoo software, designing an ERP system using Odoo software, and implementing the system that has been designed. The results of the comparative analysis between the implementation of the ERP system application and manual processes show that the advantage lies in using the ERP system application using Odoo software. This application was successfully implemented, as proven by the results of the tests carried out. This success makes a positive contribution to effectiveness and efficiency in procuring materials for service work at PT. XYZ. This research also proposes recommendations for further research, namely the creation of a comprehensive integrated system in PT business processes. XYZ. The hope is that this research can increase the effectiveness and efficiency of business processes as a whole.